The Costs of Worker Displacement - Hamermesh, Daniel S. (Quarterly Journal of Economics, 1987)
This study identifies part of the social loss attendant upon displacement as the remaining value of the assets specific to the severed employment relationship. A bargaining model is used to link wage-tenure profiles to the amount of information firms and workers possess about the duration of that relationship. If information is good, the profile will flatten as displacement approaches. Using PSID data for workers separated between 1977 and 1981, wage-tenure profiles are found not to change. This suggests that either workers, or both firms and workers, are surprised by the displacement. The present value of that part of the social loss attributable to the worker's share of firm-specific capital is around $7,000 (1980 dollars).